The financial vulnerability of non-profit entities: A theoretical framework proposal - Jimeno García, Inmaculada; Marie Garvey, Anne; Mir Fernández, Carlos; Flores Jimeno, Rocío (REVESCO. Revista de Estudios Cooperativos, 2023)
NPOs (Non-Profit Organisations) are entities created to respond to the social needs of the economy, many of which fall into financial difficulties and are forced to close. Given the importance that these entities have both socially and economically, the study of their financial vulnerability is an area of special interest. It is important to highlight the factors that characterize this type of entity in a situation of vulnerability and also to anticipate future undesirable situations which could result in closure without timely supervision. In this way, the entity could redirect its management and make the necessary changes in its structure to ensure its continuity. Our study analyses the academic literature, from a theoretical perspective, in relation to this vulnerability allowing us to construct a pentagram of five dimensions, some interrelated, which we propose to be taken into consideration in the study of an entity’s vulnerability. These five dimensions are performance, operational dimension, leverage, liquidity and most importantly reputation. This research offers a proposal to evaluate financial vulnerability in NPOs in a more comprehensive way and facilitate its management.